2021
DOI: 10.1111/jfpp.15585
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodistillation ultrasound‐assisted green extraction of essential oil from bitter orange peel wastes: Optimization for quantitative, phenolic, and antioxidant properties

Abstract: In this research, hydrodistillation ultrasonic-assisted green technique was applied to extract the essential oils from bitter orange peel. The effects of independent factors (volume/mass ratio (X 1 ), ultrasonic time (X 2 ) and hydrodistillation extraction time (X 3 )) on the quantitative, phenolic and antioxidant properties of essential oils were investigated. Linear and quadratic polynomial models with suitable ANOVA results (model p-values <0.0003, R 2 values of 0.84-0.95, adjusted R 2 values of 0.82-0.90, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Therefore, the main compound present in orange essential oil in Vietnam in this study is limonene, accounting for more than 98%, higher than in previous studies. This also helps other studies to show that oranges contain high amount of limonene, which has good fragrance, antibacterial and antioxidant properties in food, cosmetics, and pharmaceutical products [26][27].…”
Section: Assessment Of the Chemical Composition Of Optimized Oeo Samplesmentioning
confidence: 62%
See 1 more Smart Citation
“…Therefore, the main compound present in orange essential oil in Vietnam in this study is limonene, accounting for more than 98%, higher than in previous studies. This also helps other studies to show that oranges contain high amount of limonene, which has good fragrance, antibacterial and antioxidant properties in food, cosmetics, and pharmaceutical products [26][27].…”
Section: Assessment Of the Chemical Composition Of Optimized Oeo Samplesmentioning
confidence: 62%
“…In this study 2006 [27] 2010 [39] 2012 [30] 2019 [1] 2019 [3] 2020 [40] 2020 [41] 2021 [ In addition, this can also be shown that because each geographical region, climatic conditions, farming, and harvesting conditions will greatly affect the quality as well as the content of volatile compounds present in the plants.…”
Section: Citrus Limonmentioning
confidence: 68%
“…The optimal EOs have high antibacterial activity against E. coli. These bitter orange peel essential oils could be used as dietary and medicinal supplements because of their antioxidant, antibacterial properties, and healthful compositions [49] . Their influence supports the antibacterial action of essential oils on cell membrane permeability by sonochemical effect, which causes disruptions in meaningful activities such as nutrition processing, structural macromolecule synthesis, energy production, membrane transport, and growth regulators [49] .…”
Section: Antimicrobial Benefits Of Usae Bioactives From Various Food ...mentioning
confidence: 99%
“…These bitter orange peel essential oils could be used as dietary and medicinal supplements because of their antioxidant, antibacterial properties, and healthful compositions [49] . Their influence supports the antibacterial action of essential oils on cell membrane permeability by sonochemical effect, which causes disruptions in meaningful activities such as nutrition processing, structural macromolecule synthesis, energy production, membrane transport, and growth regulators [49] . The antibacterial action of essential oils is supported by their influence on cell membrane permeability, which causes disruptions in essential activities such as nutrition processing, structural macromolecule synthesis, energy production, membrane transport, and growth regulators [49] .…”
Section: Antimicrobial Benefits Of Usae Bioactives From Various Food ...mentioning
confidence: 99%
See 1 more Smart Citation